Implicit Messaging in Electronic Advertising - Hamed, Malak Ata; Shibeeb, Huda Malek (ALBAHITH ALALAMI, 2025)
This research aims to examine the techniques employed in implicit electronic advertising and how these messages are subtly conveyed to the consumer’s mind. The study focuses on analyzing the various types of such advertisements and their deployment in videos on the YouTube platform. An analytical survey method was adopted to study a sample of 237 implicit advertisements broadcast on ten channels ranked among the top 500 according to the American website Social Blade. Through the analysis of these advertisements, the research yielded several key findings. Most notably, the industrial sector dominated in terms of the number of implicit advertisements on YouTube. The study also concluded that implicit advertisements play a crucial role in self-construction; the advertising discourse is specifically directed at the individual to influence them and contribute to the formation of a new persona that aligns with the advertising messages.